Rapid initiation of antiretroviral therapy in Turkey: a modeling study - Yaylali, Emine; Erdogan, Zikriye Melisa; Calisir, Fethi; Pullukcu, Husnu; Yildirim, Figen; Inan, Asuman; Aydin, Ozlem Altuntas; Tekin, Suda; Sonmezer, Meliha Cagla; Sahin, Toros; Ozcagli, Tahsin Gokcem; Ozelgun, Berna (Frontiers in Public Health, 2024)
In order to control the HIV epidemic and reach global targets, rapid initiation of antiretroviral therapy (ART) is suggested as one of the key recommendations by policymakers.We aim to investigate the impact of rapid ART programs for individuals with an HIV diagnosis with varied coverage and initiation days after diagnosis compared to standard-of-care ART treatment in Turkey.We used a dynamic compartmental model to simulate the dynamics of HIV infection in Turkey. Rapid treatment is defined as initiation of ART within 7 days of diagnosis whereas standard-of-care treatment starts within 30 days. Three coverage levels (10%, 50% and 90%) and two rapid periods (7 and 14 days after diagnosis) have been considered and compared to standard-of-care treatment in terms of the number of HIV infections between 2020-2030.Results: Annual HIV incidence and prevalence for a 10-year period was obtained from model projections. Without a rapid ART program, the model projected around 444,000 new HIV cases while the number of cases were reduced to 345,000 (22% reduction) if 90% of diagnosed cases were included in the rapid ART program. Similarly, 10% and 50% rapid ART coverage has resulted in 3% and 13% reduction in HIV prevalence over a 10-years period.Rapid ART has a potential to alleviate rising HIV incidence for Turkey since it helps to reduce the number of infections. The benefit of rapid ART program could be substantial if the coverage of program reaches above a certain percentage of diagnosed population.